Failure to Initiate Medicine in Newly Diagnosed Hypertensives Despite Sustained High Blood Pressure in Nepal: an Under-discussed Dimension of Non-adherence - Thakur, Nishant; Budhathoki, Shyamsundar (Journal of Nepal Health Research Council, 2021)
Hypertension is growing challenge in Nepalese community which is evident from the growing concern from all sectors. Non-adherence to hypertensive medication pose challenge as patients are reluctant to start drug despite receiving physician’s advice. Continuing drug life-long once started, is a fear factor that needs dealing urgently. Keywords: Adherence; barrier; hypertension